Dengeki Daisy. Vol. 13 - Motomi, Kyousuke (Shojo beat manga., 2013)
"The past continues to haunt Teru and Kurosaki when they're given a chance to find the mysterious "M's Last Testament." Unfortunately, their savage nemesis Akira has his eyes set on finding it too! Will Akira beat them to the punch? Or does Teru have something up her sleeve?"--